Forecasting Financial Performance of Agricultural Enterprises Based on Supply Chain Operation in Seasonal Decomposition - Anna Valerievna Lyzhova; Ekaterina Ivanovna Kadochnikova; Gulnaz Zufarovna Karimova (International Journal of Supply Chain Management, 2019)
The authors used prospective estimates of revenue and expenses for ordinary activities, obtained on the basis of a multiplicative trend-seasonal model to predict the profit of an agricultural enterprise. The study draws attention to the fact that the classical decomposition of the trend-seasonal model into trend, seasonal and random components is possible and convenient for forecasting the financial performance of an agricultural enterprise that has seasonality in crop and livestock production. The forecast estimates presented in the article confirmed the main hypothesis of the study – in the presence of objective seasonal fluctuations for the agricultural enterprise, there is a tendency of growth in sales revenue while reducing costs for conventional activities. This will be possible due to the uniform production, efficient use of fixed assets, elimination of loss of working time. However, it is necessary to take into account that the agricultural sector depends on climatic conditions, and there is a risk of losses during harvesting, storage of crops – all this leads to additional costs that reduce the profits of the organization. The quality of the obtained predictive estimates is verified by the ratio of the sum of squares of absolute errors and the total sum of squares of deviations of the actual levels of the predicted value. The results of the empirical estimates confirmed the feasibility of practical use of the multiplicative trend-seasonal model, based on the classical decomposition to predict the financial performance of the agricultural enterprise.